The prominence of gender information in on-line language processing: cross-linguistic evidence of implicit gender hierarchies - Esaulova, Yulia (2014)
While social gender hierarchies and formal linguistic hierarchies are typically treated as distinct, the present work combines these theoretical notions offering a novel approach to the study of mechanisms underlying gender biases in language. Chapter 1.1 of the Introduction addresses the research on the on-line processing of gender information that is present in language. Chapter 1.2 introduces interdisciplinary aspects of the problem, relating the social cognitive notion of gender hierarchies to the linguistic and prominence hierarchies in language, and thus offers the theoretical grounding of the present research. Chapter 1.3 states the main research questions of this work and the research program. Chapter 1.4 provides the general information on the method and data analyses that were common for the reported experiments. The Overview of studies is based on a series of experiments and describes materials and main findings of Papers 1-5, as well as my contribution to each of them. The first study focuses on the recruitment of gender information for the resolution of anaphoric structures and is mainly discussed in terms of the time-course of gender processing in language. The next two studies focus on the implicit influences of gender cues in the interpretation of ambiguous structures in German and French and highlight the understanding of gender as a prominence feature and its cross-linguistic validity. The last two studies explore other representational formats of gender information and their influences. Finally, Conclusions summarize the main findings regarding explicit and implicit influences of gender information, the perspective on gender as a prominence feature, as well as limitations of the present studies and directions for future research.
Online publ.: 2015
Keywords: Hochschulschrift; Linguistik; Geschlechterforschung